Labour market performance in OECD countries: a comprehensive epirical modelling approach of institutional interdependencies - Sachs, Andreas; Schleer, Frauke (Mannheim, 2013)
"The recent economic crisis has resulted in a dramatic deterioration of economic growth and labour market performance in various industrialized countries. There is a widespread view that economies under pressure associated with high unemployment or low employment rates need to change their institutional environment. This needs to happen by conducting structural labour market reforms in order to improve labour market performance by, for instance, facilitating job reallocation processes or increasing labour market flexibility. Nevertheless, some authors argue that an institutional reform which is successful in one country might not be equally successful in another economy. A reform is assumed to depend on the country-specific institutional framework. Despite extensive theoretical and empirical contributions about the link between labour market institutions and labour market performance, evidence on the impact of changes of labour market rigidities on labour market performance which take the country-specific institutional framework and potential institutional interactions into account is still scarce. This paper contributes to the literature on interdependent institutional labour market effects by analyzing the impact of interdependencies between institutional factors for the evolution of unemployment. We follow the general theoretical model of Belot and van Ours (2004) in order to select institutional factors which are expected to have (interdependent) effects on the labour market. In order to model interactions in an econometrically correct way, we apply an innovative model selection approach to this literature, which is combined with a classical dynamic fixed-effect estimator for a two-way error component model. In doing so, we identify higher-order institutional interdependencies which matter for unemployment for a panel of 26 countries with annual data ranging from 2001 to 2008. In contrast to the previous literature, this paper is the first to focus on the impact of higher-order institutional interactions on unemployment and one of the first to consider a dynamic model specification in the context of institutional interactions. It thereby allows for a more precise and detailed analysis of the impact of interdependencies between different labour market institutions on labour market performance on a cross-country level. The results suggest that there are substantial qualitative and particularly quantitative differences across countries in the labour market impact of institutional changes for some selected institutional indicators. Hence, the impact of a reform of employment protection, unemployment benefits, labour taxes, bargaining power, and bargaining coordination crucially depends on the country-specific institutional setting. Furthermore, the findings are of considerable importance for the theoretical literature. We provide evidence for the existence of higher-order institutional interdependencies. We further document that especially for changes in employment protection and the unemployment benefit system the impact on unemployment is mixed across countries, thus questioning the relevance of best-practice policies."